Postoperative Resolution of Magnetic Resonance Imaging Signal Intensity Changes and the Associated Impact on Outcomes in Degenerative Cervical Myelopathy: Analysis of a Global Cohort of Patients. Issue 12 (15th June 2018) - Kato, So; Nouri, Aria; Reihani-Kermani, Hamed; Oshima, Yasushi; Cheng, Joseph; Fehlings, Michael G.
Abstract : Study Design: Subanalysis of the prospective AOSpine CSM North America and International studies. Objective: To describe the postoperative changes in magnetic resonance imaging (MRI) spinal cord signal intensity in degenerative cervical myelopathy (DCM) patients and to investigate the impact of its postoperative resolution on clinical outcomes. Summary of Background Data: When examining the spinal cord, hyperintensity found in MRI T2-weighted images and hypointensity in T1-weighted images are known to correlate with preoperative severity of DCM and to predict postoperative neurological recovery. However, the clinical importance of these signal intensity changes in postoperative images has not been established. Methods: Among 757 surgical DCM patients enrolled in two prospective multicenter studies, postoperative MRI images obtained between 6 and 24 months after the operation were examined with a focus on T2 hyper- and T1 hypointensity in the spinal cord. The 2-year postoperative Nurick grade, modified Japanese Orthopaedic Association score and modified Japanese Orthopaedic Association recovery rate (RR) were analyzed between patients with or without resolution of signal intensity changes. Results: A total of 167 patients with preoperative T2 hyperintensity were included with complete postoperative MRI images. Of these patients, 11% showed resolution of signal intensity changes, 70% retained T2 hyperintensity only, and 19% showed both T2 hyper- and T1 hypointensity postoperatively. There was a stepwise trend toward worse postoperative outcomes, with the no signal intensity change group showing the best outcome and the T1 hypointensity group showing the worst (mean RR: 72% vs . 51% vs . 36%, P = 0.02). Patients who exhibited resolution of T2 hyperintensity showed better outcomes than those who retained it (RR: 72% vs . 47%, P = 0.04), but the resolution of T1 hypointensity was not associated with improved outcomes (RR: 38% vs . 26%, P = 0.36). Conclusion: Postoperative resolution of T2 hyperintensity in patients with DCM was associated with the best clinical outcomes, whereas those with T1 hypointensity showed the worst. Level of Evidence: 3